Complex Pathophysiological Mechanisms and the Propose of the Three-Dimensional Schedule For Future COVID-19 Treatment - Zhou, Yonggang; Xu, Xiuxiu; Wei, Haiming (Frontiers in Immunology, 2021)
At present, the global COVID-19 epidemic is still in a state of anxiety, and increasing the cure rate of critically ill patients is an important means to defeat the virus. From an immune perspective, ARDS driven by an inflammatory storm is still the direct cause of death in severe COVID-19 patients. Although some experience has been gained in the treatment of COVID-19, and intensive COVID-19 vaccination has been carried out recently, it is still effective to save lives to develop more effective programs to alleviate the inflammatory storm and ARDS in patients with SARS-CoV-2 or emerging variants of SARS-CoV-2. In reorganizing the ARDS-related inflammatory storm formation program in COVID-19 patients, we highlighted the importance of the vicious circle of inflammatory cytokines and inflammatory cell death, which is aggravated by blood circulation to form multi-system inflammation. Summarizes the interlocking and crisscrossing of inflammatory response and inflammatory cell death mechanisms including NETs, pyrolysis, apoptosis and PANoptosis in severe COVID-19. More importantly, in response to the inflammatory storm formation program we described, and on the premise of following ethical and clinical experimental norms, we propose a three-dimensional integrated program for future research based on boosting antiviral immune response at the initial stage, inhibiting inflammatory cytokine signaling at the exacerbation stage and inhibiting cell death before it’s worse to prevent and alleviate ARDS.